2012
DOI: 10.1103/physrevlett.109.093001
|View full text |Cite
|
Sign up to set email alerts
|

Low Yield of Near-Zero-Momentum Electrons and Partial Atomic Stabilization in Strong-Field Tunneling Ionization

Abstract: We measure photoelectron angular distributions of single ionization of krypton and xenon atoms by laser pulses at 1320 nm, 0.2-1.0×10(14) W/cm(2), and observe that the yield of near-zero-momentum electrons in the strong-field tunneling ionization regime is significantly suppressed. Semiclassical simulations indicate that this local ionization suppression effect can be attributed to a fraction of the tunneled electrons that are released in a certain window of the initial field phase and transverse velocity are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 39 publications
1
61
0
Order By: Relevance
“…The phenomenon can be attributed to the high-excited Rydberg states which are deeply involved in the meV photoelectron generation. When the field frequency is larger than the frequency of the classical orbit of the Rydberg state, the electrons pumped into the Rydberg states become stabilized against ionization3334. This effect can reduce the meV electron accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…The phenomenon can be attributed to the high-excited Rydberg states which are deeply involved in the meV photoelectron generation. When the field frequency is larger than the frequency of the classical orbit of the Rydberg state, the electrons pumped into the Rydberg states become stabilized against ionization3334. This effect can reduce the meV electron accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…Recent experiments, however, have found that a significant amount of atoms can survive after the laser pulse, showing the phenomenon of tunneling without ionization [21,22]. More recently, the concept of partial atomic stabilization in tunneling ionization has been discussed [23]. The above investigations indicate that the neutral atoms or molecules might be effectively accelerated in laser fields.…”
Section: Introductionmentioning
confidence: 93%
“…In a recent publication Liu et al 19 report opposing experimental findings: they observe low yield of low kinetic energy electrons from strong-field ionization of krypton and xenon atoms using 1320 nm light and at similar pulse peak intensity as in the previously cited experimental papers. The authors attribute their contradicting observations to population trapping in high-lying (Rydberg) states as suppression mechanism.…”
mentioning
confidence: 88%